2016
DOI: 10.1080/13554794.2016.1247458
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and imaging characteristics of late onset mitochondrial membrane protein-associated neurodegeneration (MPAN)

Abstract: Young onset dementias present significant diagnostic challenges. We present the case of a 35-year-old Kuwaiti man with social withdrawal, drowsiness, irritability, anxiety, aphasia, memory loss, hypereflexia, and Parkinsonism. Brain MRI showed bilateral symmetric gradient echo hypointensities in the globi pallidi and substantiae nigrae. Left cortical hypometabolism was seen on brain fluorodeoxyglucose positron emission tomography. A cortical brain biopsy revealed a high Lewy body burden. Genetic testing reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 50 publications
(54 reference statements)
0
13
0
1
Order By: Relevance
“…Transgenic Drosophila models of MPAN manifested in a shorter lifespan and locomotor impairment, but the most remarkable trait was the accumulation of degenerative vacuoles in the brain [ 135 ]. In patients, in addition to the classical iron accumulation in SN and GP, post mortem brain examination revealed neuroinflammation marks such as α-synuclein-positive Lewy bodies, axonal spheroids and neuronal inclusions containing hyperphosphorylated tau protein [ 128 , 136 , 137 ].…”
Section: Nbia Types Related To Lipid Metabolism and Membrane Remodmentioning
confidence: 99%
“…Transgenic Drosophila models of MPAN manifested in a shorter lifespan and locomotor impairment, but the most remarkable trait was the accumulation of degenerative vacuoles in the brain [ 135 ]. In patients, in addition to the classical iron accumulation in SN and GP, post mortem brain examination revealed neuroinflammation marks such as α-synuclein-positive Lewy bodies, axonal spheroids and neuronal inclusions containing hyperphosphorylated tau protein [ 128 , 136 , 137 ].…”
Section: Nbia Types Related To Lipid Metabolism and Membrane Remodmentioning
confidence: 99%
“… Gore, E. et al, 2016. [ 57 ] Case report MPAN 1M 35 Kuwaiti NA Early behavioural change. Hayflick, S.J.…”
Section: Table A1mentioning
confidence: 99%
“…Previous studies in MPAN using clinical MRI at 3.0 T showed caudate iron accumulation only in late-onset or long-standing cases. 5 In this study, taking advantage of the enhanced sensitivity to iron-induced field inhomogeneities at ultrahigh magnetic field strengths, we have shown that caudate nucleus iron accumulation is a common feature of MPAN patients with typical age at onset and relatively short disease duration. None of the patients displayed an "eye-of-the-tiger sign," which is considered to be pathognomonic of PKAN, but has also been observed, albeit in a less pronounced form, in MPAN.…”
Section: Mpan Findingsmentioning
confidence: 79%
“…In this study, however, we detected early susceptibility changes in the caudate nucleus and putamen of heterozygous mutation carriers in the absence of detectable atrophy, suggesting that iron deposition may be an upstream event preceding cell loss in the caudate nucleus of MPAN patients. Previous studies in MPAN using clinical MRI at 3.0 T showed caudate iron accumulation only in late‐onset or long‐standing cases . In this study, taking advantage of the enhanced sensitivity to iron‐induced field inhomogeneities at ultrahigh magnetic field strengths, we have shown that caudate nucleus iron accumulation is a common feature of MPAN patients with typical age at onset and relatively short disease duration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation